Analisis Strategi Usaha Ayam Petelur Dalam Mendukung Ketahanan Pangan Dan Ketahanan Nasional Di Desa Mangunrejo, Kecamatan Gurah, Kabupaten Kediri, Jawa Timur - Elvina Aulia; Revalina Yulia Indiarti; Puji Apriyanti; Xenia Regyta Dahayu; Endah Luthfi Fitriani (Jurnal Ilmu Peternakan Indonesia, 2026)
This study aims to analyze the business strategies of a laying hen farm in supporting food and national security, focusing on the case of Mrs. Mumpuni’s farm in Mangunrejo Village, Gurah District, Kediri Regency, East Java. A qualitative approach utilizing the case study method was employed. Data were gathered through in-depth interviews, field observations, and documentation, then analyzed using the Miles and Huberman model, which encompasses data reduction, data display, and conclusion drawing. The findings indicate that business sustainability is supported by the implementation of a nucleus-plasma partnership system, independent feed formulation, income diversification through the utilization of waste as organic fertilizer, and effective livestock health management. These strategies enhance business resilience against price fluctuations, the pandemic, and various operational challenges. The farm contributes to food security by providing a sustainable source of animal protein and creating jobs, while also strengthening the local economy—thereby supporting national security in alignment with Pancasila values. The study recommends implementing digital financial management, enhancing biosecurity measures, utilizing temperature-control technology for the coop, and strengthening security systems to further ensure the sustainability of small-scale poultry farming.